Life history and functional response of Acarinus philippinensis Kapur (Coleoptera:Coccinellidae) on Aphis gossypii Glover (Hemiptera Aphididae) - Lapiz, R.V.; Gapud, V.P. (Philippines Rushing Water Publishers, 1995)
"The life history, consumption capacity and functional response of Acarinus philippinensis Kapur (Coleoptera:Coccinellidae) were studied, using Aphis gossypii Glover (Hemiptera:Aphididae) as prey species and wild pepper as host plant. The different developmental stages are described. The total developmental period (generation time) ranged from 14 to 18 days. The adult span was 47-52 for males and 48-55 days for females. Fecundity ranged from 140 to 235 eggs. The consumption capacities of larval instars were: 1st instar, 1-5 aphid nymphs; 2nd instar, 3-9; 3rd instar, 6-10; and 4th instar, 8-17 for day 1, 12-27 for day 2, and 15-31, with a total consumption at larval stage of 38-97 aphid nymphs. The consumption capacity of adults per pair was 113-157 nymphs from emergence to pre-mating, while that of females was 35-78 after pre-mating to preovidposition. The total number of aphids consumed by A. philippinensis from 1st to instar to death were 1376-1431 for males and 1478-1852 for females. the functional responses of A. philippinensis were generally directly proportionate to the prey density as the developmental stages progressed (Type II). Aphid prey size and stages influenced the consumption rate of the larvae as they progressed, with proportionate increase in preference for nymphs over adults."
Keywords: Coccinellid beetle; Coleoptera; Homopterous insect